Effectiveness of screening for colorectal cancer with a faecal occult-blood test, in Finland - J Pitkäniemi; K Seppä; M Hakama; O Malminiemi; T Palva; M-S Vuoristo; H Järvinen; H Paimela; P Pikkarainen; A Anttila; L Elovainio; T Hakulinen; et al. (BMJ Open Gastroenterology)
Background Screening for colorectal cancer (CRC) with guaiac-based faecal occult-blood test (FOBT) has been reported to reduce CRC mortality in randomised trials in the 1990s, but not in routine screening, so far. In Finland, a large randomised study on biennial FOB screening for CRC was gradually nested as part of the routine health services from 2004. We evaluate the effectiveness of screening as a public health policy in the largest population so far reported.Methods We randomly allocated (1:1) men and women aged 60–69 years to those invited for screening and those not invited (controls), between 2004 and 2012. This resulted in 180 210 subjects in the screening arm and 180 282 in the control arm. In 2012, the programme covered 43% of the target age population in Finland.Results The median follow-up time was 4.5 years (maximum 8.3 years), with a total of 1.6 million person-years. The CRC incidence rate ratio between the screening and control arm was 1.11 (95% CI 1.01 to 1.23). The mortality rate ratio from CRC between the screening and control arm was 1.04 (0.84 to 1.28), respectively. The CRC mortality risk ratio was 0.88 (0.66 to 1.16) and 1.33 (0.94 to 1.87) in males and females, respectively.Conclusions We did not find any effect in a randomised health services study of FOBT screening on CRC mortality. The substantial effect difference between males and females is inconsistent with the evidence from randomised clinical trials and with the recommendations of several international organisations. Even if our findings are still inconclusive, they highlight the importance of randomised evaluation when new health policies are implemented.Trial registration 002_2010_august.